The development of learning video media based on swishmax and screencast o-matic softwares through the contextual approach - Kholifah, Siti (Dinamika Pendidikan, 2016)
The low learning outcomes as a result of low studentsâ interest in learning on the Organizational Behavior subject was the background of the study. The objective of the study was to develop a learning media video based on swishmax dan screencast o-matic softwares through the contextual approach. The study used the ADDIE development model which consisted of five stages: Analysis, Design, Development, Implementation, and Evaluation. Before using, the learning video media first tested Â by the media experts and the subject experts. Then; it needed studentsâ feedback on questionnaires about the media. The results of theÂ  experts, and studentsâ questionnaires showed that the media was very good and feasible to be used. The effectiveness of the media was analyzed by t-test. It obtained the mean score of experimental class was 85.03; whereas the mean score of control class was only 79.00. By using the t test scores was 3.30> 1.997; then Ho was rejected. Therefore; it can be concluded that learning by using the learning video media based swishmax and screencast o-matic softwares through the contextual approach was better than the conventional teaching on Organizational Behavior.Rendahnya hasil belajar sebagai akibat dari rendahnya minat belajar mahasiswa pada mata kuliah perilaku organisasi adalah hal yang mendasari dilakukannya penelitian ini. Penelitian ini bertujuan untuk mengembangkan media video pembelajaran berbasis Software Swishmax dan Screencast O-matic dengan pendekatan kontekstual. Pada penelitian ini menggunakan model pengembangan ADDIE dimana dalam tahapnya terdiri dari 5 tahapan yaitu analisis, desain, development, implementasi, evaluasi. Sebelum digunakan, media video pembelajaran terlebih dahulu dilakukan uji validasi oleh ahli media dan ahli materi. Selain itu diperlukan juga angket tanggapan mahasiswa mengenai media tersebut. Hasil dari validasi ahli media, materi dan angket mahasiswa berkriteria sangat baik dan layak untuk digunakan. Uji keefektifan media menggunakan uji t pihak kanan, diperoleh rata-rata hasil belajar kelas eksperimen 85,03, dan kelas kontrol adalah 79,00. Dengan analisis menggunakan uji t diperoleh nilai ttabel < thitung yaitu 3,30> 1,997maka H0 ditolak, sehingga dapat disimpulkan bahwa pembelajaran dengan menggunakan media video pembelajaran berbasis Software Swishmax dan Screencast O-matic dengan pendekatan kontekstual lebih baik dibandingkan dengan pembelajaran konvensional pada mata kuliah perilaku organisasi.